Aberrant TDP‐43 phosphorylation: a key wind gap from TDP‐43 to TDP‐43 proteinopathy. Issue 2 (28th June 2021) - Huang, Zi‐Qi; Ba, Zhi‐Sheng; Huang, Nan‐Qu; Li, Yuan‐Yuan; Luo, Yong
Abstract : TDP‐43 proteinopathy is a kind of neurodegenerative diseases related to the TAR DNA‐binding protein of 43‐kDa molecular weight (TDP‐43). The typical neurodegenerative diseases include amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), Alzheimer's disease (AD), Parkinson's disease (PD) and so on. As the disease process cannot be blocked or slowed down, these patients have poor quality of life and poor prognosis, and bring a huge burden to the family and society. So far, the specific pathogenesis of TDP‐43 proteinopathy is not clear, and there is no effective preventive measure and treatment program for this kind of disease. TDP‐43 plays an important role in triggering or promoting the occurrence and progression of TDP‐43 proteinopathy. The hyperphosphorylation of TDP‐43 is undoubtedly an important factor in triggering or promoting the process of TDP‐43 proteinopathy. Hyperphosphorylation of TDP‐43 can inhibit the degradation of TDP‐43, aggravate the aggregation of TDP‐43 protein, increase the wrong localization of TDP‐43 in cells, and enhance the cytotoxicity of TDP‐43. More and more evidences show that the hyperphosphorylation of TDP‐43 plays an important role in the pathogenesis of TDP‐43 proteinopathy. Inhibition of TDP‐43 hyperphosphorylation may be one of the important strategies for the treatment of TDP‐43 proteinopathy. Therefore, this article reviews the role of TDP‐43 phosphorylation in TDP‐43 proteinopathy and the related mechanisms.